THE INFLUENCE OF SHIATSU TECHNIQUE ON THE TIME OF EXPENDITURE OF ASI IN POST PARTUM MOTHER IN MOJOKERTO DISTRICT - Catur Prasastia lukita Dewi Dewi; INDAH LESTARI LESTARI; AYU TRI WIDIYANTI (INTERNATIONAL JOURNAL OF NURSING AND MIDWIFERY SCIENCE (IJNMS), 2018)
Late delivery of breast milk is a common problem in postpartum mothers and may result in early breastfeeding unfulfilled resulting in adverse health effects for both mother and baby. Shiatzu Techniqu is one form of non-pharmacologic therapy to accelerate the expenditure time of breast milk. This study aims to determine the influence of Shiatzu Technique in accelerating the time spent on breastfeeding post partum mother. This research type is quasi experiment with Post Control Only Control With Group Design design, with two groups each consisting of 80 respondents taken with concecutive technique. Data analysis using T-Two Sample Test as comparative test and expenditure time of ASI on control group that did not done shiatzu technique and experiment group performed shitzu technique with Î± <0.05. The results of the differences from both groups were tested with T-Two Sample Test with the result value Ï = 0.003. The result of the differences from both groups tested with T-Two Sample Test with the result value Ï = 0.003 means there is a significant difference between the control group and the experimental group. In the control group most of the time Breastmilk expenditure was Normal (25-72 hours) whereas in the experimental group its Rapid Breastfeeding (1-24 hours). Faster breastfeeding time in the post partum mothers of the experimental group was due to two interventions given that early Initiation of Breastfeeding was also continued by Shiaztu Technique. Thus, in postoperative mothers with no contraindications, Shiatzu Technque was very effective given to speed up the release of breast milk.